Penerapan Ijarah Muntahiya Bit Tamlik pada Perusahaan Leasing dalam Perspektif Fikih Muamalah: Studi Kasus PT. Adira Finance - Hendra, Hendra; Putri, Rafika Chudriana; Sudiarti, Sri; Marliyah, Marliyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Currently, human needs are increasingly complicated, especially for vehicles as a means of support in every activity. Therefore, the role of Islamic financial institutions in this case is needed as a facilitator for people who are constrained by capital. Islamic financial institutions have a financing agreement